Ventrally Fused Conjoined Twins (Omphaloischiopagus): A Roadmap to Successful Separation - Amr A. AbouZeid; Shaimaa A. Mohammad; Ahmed B. Radwan; Leila ElDieb; Yasmin G. El-Gendy; Hanan Ibrahim; Akram Amer; Tarek Shabana; Hany Elzahaby; Amir Elbarbary; Mohamed Saleh; Tarek H. Abdelaziz; et al. (Georg Thieme Verlag KG, 2022)
Conjoined twining is one of the most fascinating and challenging situations which a pediatric surgeon may face in his career. Only few surgeons may have the opportunity to share in separation of such cases. In this report, we aim to share our experience with the successful separation of ventrally fused male conjoined twins (omphaloischiopagus). The case was thoroughly studied via preoperative cross-sectional imaging modalities (magnetic resonance imaging [MRI] and computed tomography [CT] angiography), complemented by data obtained from reviewing similar cases in the literature. A clear delineation of the complex anatomy was achieved preoperatively which proved to be well consistent with the operative findings. A detailed description of the operative procedure to divide/redistribute the shared abdominal/pelvic organs between both twins is provided. To the best of our knowledge, this is the first report to describe the detailed and unique internal anatomy of a common central phallus associating ischiopagus conjoined twins. The penis was centrally located in the perineum in between both twins with an open urethral plate. This common phallus had a peculiar configuration with four crura anchoring ischial bones of both twins together.